Critical and experimental study in the development of moral ideas - Miller, Ross (The University of Edinburgh, 1928)
This study makes no attempt at a comprehensive history of ethics. It rather approaches some representative theories from the standpoint of the thesis that morality is the socialized behaviour of the integrated personality. The interest is primarily in what tendencies these various theories consider to be innate in man; in their treatment of the socialization of the individual; and of the integration of the personality; in their suggested solutions to the ego -alter conflict; and in their consideration of religion as an integrative force within the personality. The experimental section makes no attempt to measure morality or moral traits, for it is difficult, if indeed it be possible, for a laboratorial test situation, which would be a necessary prerequisite to such measurement, to elicit natural moral reactions from subjects. Furthermore, the objective measurement of morality would necessitate the establishment of a norm as a standard which, when it has been secured, is, after all, a somewhat arbitrary gauge for measuring what many think to be incommensurable. Henri Clavier (1) speaks to the point in these words: "There is no algebra or arithmetic of the soul, neither a physics, a chemistry, nor a physiology". This study, rather, tries to discover what development of moral ideas takes place in the mind of the child in early adolescence, in that period of growth when self -consciousness and moral responsibility are thought to become manifest. The method used is the group questionnaire. Since words are but the symbols of ideas, it is assumed that ethical ideas and moral vocabulary develop together. It may be objected that words carry varying shades of meaning for various children; but this difficulty inheres in language itself. It may be further held that the questionnaire measures intelligence by means of a moral vocabulary; but even if this be the case, such measurement of intelligence does not exclude a simultaneous measurement of moral ideas. The questions of the test are based upon the theory that central to the development of moral behaviour is the development, within society, of the self-regarding sentiment. Some writers hold that morality is merely custom, a social phenomenon. Others hold that ethics treats of what ought to be, that it is constituted of those principles which determine the true worth of ultimate ends of conduct. The present essay presents the thesis that the criteria of morality are two: first, socialization of behaviour; second, integration of the personality around a worthy master sentiment. Although "meta- psychological" theories are not legitimately a part of psychology, this essay, in one instance, dares to trespass slightly upon metaphysical territory, because in this case that field is not wholly foreign to the present thesis. This transgression is noted where made. "Ideas" are considered to be simply the conditions of one's thinking upon any subject - the " enduring cognitive dispositions and systems of dispositions " "Concepts ", in addition, are thought of as partaking of the nature of the universal rather than of the particular. "Ideals" are those constructs of the imagination and reflection which embody highest values; they serve as archetypes for the determination of the copy. ideals are mental constructs " in which needs find their fulfilment".
A critical and experimental study in the development of moral ideas